2020
DOI: 10.1016/j.jsxm.2020.07.083
|View full text |Cite
|
Sign up to set email alerts
|

Pericyte-Derived Extracellular Vesicle–Mimetic Nanovesicles Restore Erectile Function by Enhancing Neurovascular Regeneration in a Mouse Model of Cavernous Nerve Injury

Abstract: Background Extracellular vesicle (EV)–mimetic nanovesicles (NVs) from embryonic stem cells have been observed to stimulate neurovascular regeneration in the streptozotocin-induced diabetic mouse. Pericytes play important roles in maintaining penile erection, yet no previous studies have explored the effects of pericyte-derived NVs (PC-NVs) in neurovascular regeneration in the context of erectile dysfunction. Aim To investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…The diameter of the purified PC-NVs was ~30 nm. As previous studies have shown, the NVs also expressed EV surface markers, such as Alix, TSG101 and CD81 ( 17 , 18 ). Therefore, the extracted PC-NVs were characterized by western blot analysis.…”
Section: Resultsmentioning
confidence: 53%
See 2 more Smart Citations
“…The diameter of the purified PC-NVs was ~30 nm. As previous studies have shown, the NVs also expressed EV surface markers, such as Alix, TSG101 and CD81 ( 17 , 18 ). Therefore, the extracted PC-NVs were characterized by western blot analysis.…”
Section: Resultsmentioning
confidence: 53%
“…Therefore, to overcome this limitation, a mini extruder system was developed, and >100-fold greater EV-mimetic NVs were extracted from different cell types, such as embryonic stem cells (ESCs) and mouse cavernous pericytes (MCPs). In addition, ESC-derived EV-mimetic NVs (ESC-NVs) and MCP-derived EV-mimetic NVs (PC-NVs) showed similar qualities to natural EVs, thus might be helpful for studies on neurovascular regeneration ( 17 , 18 ). However, the detailed molecular mechanisms by which PC-NVs promote nerve regeneration remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings suggest that different antiangiogenic and molecular targets produce different results in the treatment of fibrosis. We recently reported in a mouse model of diabetic ED that pericyte-derived angiogenic factor restored erectile function by enhancing cavernous angiogenesis [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The cell-derived EV–mimetic NVs showed similar characteristics to the natural EVs [ 22 ]. We recently demonstrated that intracavernous injection of PC–NVs induced penile angiogenesis and rescued erectile function in a mouse model of cavernous nerve injury [ 15 ]. Along with potential relationship between angiogenesis and suppression of tissue fibrosis [ 11 13 ], the angiogenic potential of pericytes and PC–NVs led us to investigate the potential role of PC–NVs in the fibrogenic process of PD.…”
Section: Introductionmentioning
confidence: 99%